PERTANGGUNGJAWABAN PIDANA MENYALAHGUNAKAN KEWENANGAN YANG MENGAKIBATKAN MERUGIKAN KEUANGAN NEGARA (ANALISIS PUTUSAN NOMOR: 85/PID. SUS-TPK/2018/PN MDN) - Hasibuan, Ardiansyah; Nadirah, Ida (JURNAL DOKTRIN REVIEW, 2023)
Corruption is closely related to the abuse of authority or influence that exists in a person's position as an official which deviates from legal provisions so that these actions have harmed the State's finances. The formulation of the problem is how to criminalize abuse of authority which results in harm to the State's finances, and what criminal responsibility is in cases of criminal acts of corruption committed due to abuse of authority, as well as how judges consider in cases of criminal acts of corruption committed due to abuse of authority in case Number: 85/Pid.Sus-Tpk/2018/PN.Mdn). The research method used is normative legal research. In relation to the criminal regulation of abusing authority which results in harm to the State's finances, it is regulated in Article 3 of the Corruption Law and the criminal responsibility for corruption with the mode of abuse of authority under Article 3 of the Corruption Law must have an element of every person who has authority, so that the conditions for a person to be declared to have violated Article 3 namely that he must have the authority, position, title and consideration of the Panel of Judges in cases of criminal acts of corruption committed due to abuse of authority in case Number: 85/Pid. Sus-Tpk/2018/PN.Mdn), Defendant "AS" was not legally and convincingly proven guilty of committing a crime as in the Primair indictment, however, Defendant "AS" was declared by the Panel of Judges to be legally and convincingly proven guilty of committing the crime of "Corruption abuseof authority” as stated in the indictment of the Subsidiary Public Prosecutor. So, as a suggestion, there should be regulations established so that the Prosecutor's Office is given the authority to supervise State Officials as the Authority for Using the Budget, since they are about to make policies, so that there are no abuses of authority that result in harm to State finances.